Discordance in prognostic ability between physician assessed NYHA classification and self-reported health status in patients with acute heart failure. (14th October 2021) - Belkin, M; Wussler, D; Kozhuharov, N; Strebel, I; Walter, J; Michou, E; Goudev, A; Menosi Gualandro, D; Maeder, M; Kobza, R; Rickli, H; Breidthardt, T; et al.
Abstract: Background: Especially in patients with acute heart failure (AHF) the NYHA classification remains of uncertain representation of patients' actual health state. Alternatively, patient's subjective well-being, in terms of health-related quality of life (HRQL), showed to have an excellent prognostic ability in out clinic patients with chronic heart failure. Objectives: It is unknown whether HRQL instruments can assess a more reliable prognostication in patients hospitalized due to AHF than the NYHA classification. Methods: Goal Directed Afterload Reduction in Acute Congestive Cardiac Decompensation Study (GALACTIC) was a multicenter, randomized, open-label blinded-end-point trial that emphasized early intensive and sustained vasodilation in adult patients hospitalized due to AHF with NYHA functional class III/IV, however provided neutral findings. HRQL was assessed by the generic EQ-5D-3L which is a 3-leveled 5-item instrument and the disease-specific Kansas City Cardiomyopathy Questionnaire (KCCQ). Unadjusted and adjusted Cox regression models were performed after patients were grouped into low (EQ-5D −0.074<0.25; KCCQ 0<25), moderately low (0.25<0.5; 25<50), moderately high (0.5<0.75; 50<75) and high HRQL (0.75–1.0; 75–100). Results: 781 patients were enrolled in 10 centres in 5 countries over 2 continents among which 536 (69%) patientshad completed theEQ-5D and 419 (54%) the KCCQ shortly after admission. Within 180 days of follow-up69 (13%) and 54 (13%) patients died and 151 (28%) and 122 (29%) died or were rehospitalized due to AHF, respectively. Cumulative incidence as well as HRs in patients grouped according to NYHA (n=536) indicated a comparable or significantly lower risk in patients with NYHA IV: e.g. for the combined outcome HR 1.07 (95% CI 0.777–1.473) and aHR 0.463 (95% CI 0.245–0.875). Whereas HRs in patients grouped according to both, EQ-5D (n=536) and KCCQ (n=419), increased from the group with highest to the group with the lowest HRQL: e.g. aHR for moderately high 1.11 (95% CI 0.718–1.715), for moderately low 1.721 (95% CI 1.102–2.688) and for low EQ-5D index 1.891 (95% CI 1.136–3.149) referenced to high HRQL (EQ-5D index 0.75–1.0). Conclusions: These findings corroborate and extend previous work suggesting that NYHA classification poorly discriminates AHF patients' prognosis and challenge its' extensive application. HRQL might be a possible alternative to easily assess these patients' heath state. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science Foundation, the Swiss Heart Foundation